Teacher’s Strategy In Class Learning at Madrasah Tsanawiyyah Amaliyah Medan Sunggal - Febri Nanda Monalisa; Ahmad Raihan Azizi; Rio Febriyan; Risa Adela (Educan : Jurnal Pendidikan Islam, 2022)
Abstract: The emergence of various obstacles felt by students in the learning process is inseparable from the importance of the application of good learning strategies in the classroom. Therefore, so that the learning and teaching process becomes effective and efficient and does not cause saturation for teacher students required to be able to use the appropriate and pleasant learning strategies in teaching in the classroom. The researcher formulated the purpose of this study wasto: (1) the application of the learning strategy carried out by Teachers in Madrasah Tsanawiyah Amaliyah, (2) What form of evaluation is carried out by the teacher in an effort to improve classroom learning strategies at Madrasah Tsanawiyah (MTs) Amaliyah Sunggal so that learning outcomes are maximized?. This type of research is qualitative, with the research subject of teachers. And data were collected by interview and field observation with relevant themes. The results of this study indicate that: 1) The use of the lecture method in the learning process by the teacher 2) The use of a character approach in facilitating the achievement of learning objectives 3) The use of the method of forming study groups for students who have difficulty in absorbing learning materials 4) The form of evaluation made is by how to evaluate each end of the lesson chapter and at the mid-semester and end-semester evaluations. Keywords: Learning Strategies; Classromm Learning; Learning Evaluation